Usefulness of the Kyoto Classification Score for Prediction of Current Helicobacter pylori Infection - Heejun Kang; Chul-Hyun Lim; Sukil Kim; Arum Choi; Jung-Hwan Oh (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Background/Aims: Based on the Kyoto classification of gastritis, mucosal atrophy, endoscopic intestinal metaplasia, fold enlargement, nodularity, and diffuse redness may be associated with gastric cancer and Helicobacter pylori (H. pylori) infection. In this study, we investigated the association between Kyoto scores based on the aforementioned five variables and current H. pylori infection. Materials and Methods We reviewed medical records of consecutive patients who underwent endoscopic biopsies between January and June 2019. The study included 687 patients (370 and 317 patients with H. pylori-negative and -positive results, respectively). The Kyoto score was evaluated by the endoscopist who performed the test and was reconfirmed by another endoscopist. The total Kyoto score was analyzed using a receiver operating characteristic (ROC) curve for each score from 0 to 8. Multivariate analysis was used to determine the variables associated with H. pylori infection. Results: The maximum value of the Youden index (which reflects the ideal cut-off score of the Kyoto score on the ROC curve) was a Kyoto score of 2 points (Youden index 0.5905). Nodularity (OR 24.69, 95% CI 8.57~71.16, P<0.001) and diffuse redness (1 point: OR 18.29, 95% CI 10.29~32.52, P<0.001 and 2 points: OR 30.82, 95% CI 14.07~67.52, P<0.001) showed the highest OR on multivariate analysis. Conclusions: A Kyoto classification cut-off score of 2 points was suggestive of H. pylori infection, and mucosal nodularity and diffuse redness were most significantly associated with the risk of infection.